Results of the use of post-surgical thermotherapy in oral surgery. Cienfuegos, 2015-2016 - Ramón Ahmed Pérez García; Blas Jorge González Manso (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Foundation: In oral surgery different variants of thermotherapy are used to relieve postoperative symptoms. The opinions and ways of acting are diverse, and depend on the conditions of the environment, on the surgical pathologies, even on the patient's. Objective: to describe the results of thermotherapy use as a post-surgical treatment in oral surgery. Methods: It is a descriptive, series of case studies, carried out between October 2015 and October 2016, in the Maxillofacial Surgery service of the Provincial Hospital of Cienfuegos. The 120 patients included were divided into four groups of 30. The variables were based on symptomatic triad pain, inflammation and functional impotence; and were evaluated for the different treatment groups at 72 hours and seven days after surgery. Results: after seven days, 50% of the patients who received combined thermotherapy did not have inflammation, and 80% of those who received cold thermotherapy did not report pain. Cold thermotherapy application was influenced the most in reducing functional impotence in both evaluations; Seven days after, 76.7% of this group did not report such symptoms. Conclusion: The use of thermotherapy in this series was effective in improving the symptoms and signs evaluated. The best results were evident in the case of combined thermotherapy, associated with less inflammation; and cold thermotherapy, which allowed a decrease in pain and functional impotence.